Knowledge and attitude towards HIV post exposure prophylaxis (PEP) among healthcare workers in Hospital Pakar Universiti Sains Malaysia - Faizal, Muhammad Harith Danial Mohd (Universiti Sains Malaysia, 2025)
This study aimed to assess the knowledge and attitude towards HIV post-exposure prophylaxis (PEP) among healthcare workers (HCWs) at Hospital Pakar Universiti Sains Malaysia (HPUSM). As HCWs are at risk of occupational exposure to HIV, especially through needle-stick injuries, understanding their awareness and perception of PEP is crucial. A cross-sectional study was conducted involving 167 participants, selected through stratified random sampling from seven inpatient wards. Data were collected using a structured questionnaire and analysed using descriptive statistics, Pearson correlation, and Chi-square tests. The results showed that while 80.2% of HCWs had a favourable attitude towards PEP, only 44.9% demonstrated good knowledge, with the majority 55.1% lacking adequate understanding. Although 76.6% had heard of PEP, only 9.6% had received formal training, and 71.3% had not encountered current PEP guidelines. A significant moderate positive correlation was found between knowledge and attitude (r² = 0.292, p = 0.001). Additionally, knowledge was significantly associated with factors such as educational level, profession, exposure to PEP information, and familiarity with guidelines. However, no socio-demographic characteristics were significantly associated with attitude. The findings highlight the need for improved training, clearer protocols, and greater institutional support to enhance PEP knowledge and readiness among healthcare workers